RESONANT SLOSHING IN SHALLOW-WATER - Ockendon, H; Ockendon, J; Johnson, A (1986)
The ordinary differential equation which represents forced water waves on shallow water near resonance, is considered when the dispersion is small. Asymptotic methods are used to show that there are multiple solutions with period 2 pi for a given value of the detuning parameter. The effects of dissipation are also considered.